2023
DOI: 10.1186/s12967-023-03887-0
|View full text |Cite
|
Sign up to set email alerts
|

The persistent viral infections in the development and severity of myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: Background Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a multifactorial disease with an unexplained aetiology in which viral infections are possible trigger factors. The aim of this study was to determine the involvement of human herpesvirus (HHV)-6A/B, HHV-7, and parvovirus B19 (B19V) in the etiopathogenesis of ME/CFS. Methods 200 patients with clinically diagnosed ME/CFS and 150 apparently healthy individuals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Recent research suggest that EBV may be an important risk factor for the development of ME/CFS – at least in a sub-group of patients, linked with immune dysfunctions and/or genetic predisposition, and could contribute to the observed neuro-immunological impairments seen in ME/CFS patients [ [54] , [55] , [56] , [57] ]. A review by Rasa et al (2021) showed that viral diseases such as human herpesviruses, enteroviruses and huan parvovirus B19 were associated with ME/CFS onset and likely caused the irreversible immunological impairments observed, rather than causing chronic or latent viral infections [ 58 ]. Several other agents have been associated with ME/CFS in the literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggest that EBV may be an important risk factor for the development of ME/CFS – at least in a sub-group of patients, linked with immune dysfunctions and/or genetic predisposition, and could contribute to the observed neuro-immunological impairments seen in ME/CFS patients [ [54] , [55] , [56] , [57] ]. A review by Rasa et al (2021) showed that viral diseases such as human herpesviruses, enteroviruses and huan parvovirus B19 were associated with ME/CFS onset and likely caused the irreversible immunological impairments observed, rather than causing chronic or latent viral infections [ 58 ]. Several other agents have been associated with ME/CFS in the literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, autoimmunity driven by defective B-cell functioning is suspected to bring about autoreactivity which in turn contributes to symptom manifestation [ 127 , 230 , 256 , 257 ]. There are many other studies demonstrating increased antibody levels directed at herpesviruses (not only EBV) in ME/CFS [ 30 , [258] , [259] , [260] , [261] , [262] , [263] ]. More recent studies have identified herpesvirus nucleic acids and antigens, in significant concentrations, in ME/CFS tissue [ 32 , 60 , 263 , 264 ].…”
Section: Viruses: How Are They Involved and Where Are They Hiding?mentioning
confidence: 99%
“…There are many other studies demonstrating increased antibody levels directed at herpesviruses (not only EBV) in ME/CFS [ 30 , [258] , [259] , [260] , [261] , [262] , [263] ]. More recent studies have identified herpesvirus nucleic acids and antigens, in significant concentrations, in ME/CFS tissue [ 32 , 60 , 263 , 264 ]. Rasa- Dzelzkaleja et al (2023) showed that 45% of ME/CFS individuals within their study were experiencing reactivation of herpesviruses (HHV-6 and HHV-7), and that these individuals expressed higher proinflammatory markers (IL-6, TNF-α) than those ME/CFS individuals with latent infection.…”
Section: Viruses: How Are They Involved and Where Are They Hiding?mentioning
confidence: 99%
“…Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a chronic condition characterized by unresolved fatigue, cognitive dysfunction, malaise, orthostatic issues, and post-exertional symptom exacerbation (PESE), among other symptoms [ 1 ]. The etiological cause is officially unknown, but viral infection is believed to be a precipitating factor, and its pathology is very much associated with viral activity [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, here, we aim to focus on herpesviruses and the endothelium or associated tissues. There are a number of different herpesviruses, but the focus here is on the ones significantly implicated in ME/CFS, namely HHV-4 (EBV) and HHV-6 [ 2 , 3 , 4 , 5 , 57 , 58 ]. For an overview of the ideas presented in this paper, as well as a mind map for clarification, see Figure 1 .…”
Section: Introductionmentioning
confidence: 99%